Acting Women: Gender Roles in Ana Istarú’s Hombres en escabeche, Elena Garro’s La señora en su balcón, and Carmen Boullosa’s Cocinar hombres - Miller, Elaine M. (Latin American Theatre Review, 2010)
Ana Istarú’s Hombres en escabeche (2000) combines humor and serious commentary to break down the binary division of gender roles in Costa Rican society. This essay explores key commonalities in this play and Mexican playwrights Elena Garro’s La señora en su balcón (1963) and Carmen Boullosa’s Cocinar hombres (1987). The three plays develop metaphors involving food to express the confining roles traditionally assigned to women and to eventually transform them into acts of creative independence. Although the decisive actions taken by the female protagonists, who are conscious of the performative nature of gender and refuse to play the roles assigned to them by patriarchal culture, and their approach to calling for social changes vary, all of these plays conclude with their empowerment. (EMM, Article in English)